Variation-Difference Method of Calculation of Layered Rubber-Metal Vibration Isolators Used for Protection of Reinforced Concrete Buildings from Anthropogenic Vibration - D. K. Sizov (Железобетонные конструкции, 2024)
In the modern construction complex of the city of Moscow for the protection of buildings and structures from man-made vibration arising from the movement of trains of rail transportation (subway trains, railroad lines and trams). To protect buildings and structures from anthropogenic vibration arising from the movement of rail transport trains (subway trains, railroad lines and streetcars), Moscow uses layered rubber-metal vibration isolators [1]. Most often, to determine their static and dynamic characteristics, the finite element method (FEM) is used, which makes it possible to determine all components of the stress-strain state and frequencies of free oscillations in the loaded state practically for any structural forms of isolators. However, for the most popular software packages that implement FEM, the problem of optimizing the structural shape of the vibration isolator still requires significant time expenditures for multiple changes of the finite element mesh, repeated setting of boundary conditions and implementation of a series of calculations. Only some of the software packages implementing the FEM solve optimization problems of the shape of the product being calculated, most often it is related to foreign software products with universal functionality. Variation-difference method (VDM) is the closest to the finite element method (FEM) in terms of its computational capabilities. It is possible to create program modules that repeatedly and automatically solve three-dimensional problems of elasticity theory taking into account the changed geometry of the vibration isolator: the dimensions of the product, the location of perforations within the rubber layers, as well as the thickness of the rubber layer and other parameters important for obtaining an effective technical solution for vibration isolation of buildings. Further, the article describes the method of implementation of the variational-difference method (VDM) as applied to the solution of the problem of determining the components of the stress-strain state inside a three-dimensional layered vibration isolator with perforations of different sizes having different locations relative to the contour of the vibration isolator, i.e., the solution of the problem of optimizing the three-dimensional shape of the vibration isolator is given.